Methane Concentration and Chronology from the WAIS Divide Ice Core (WDC05A) - Mcconnell, Joseph; Brook, Edward J; Mitchell, Logan E; Sowers, Todd A.; Taylor, Kendrick C. (IEDA: US Antarctic Program Data Center, 2011)
Abstract: This data set provides a high-precision and high-resolution record of atmospheric methane from the West Antarctic Ice Sheet (WAIS) Divide ice core WDC05A, spanning the years 1000 to 1800 C.E. The data include methane (CH4) concentration measurements and ice age chronology. Methane concentration data include mean sample depth, gas age, mean concentration, and concentrations from individual measurements, at a temporal resolution of approximately nine years. Ice chronology data include depth and ice age. Data are available via FTP, in Microsoft Excel (.xlsx) format.